Immunoregulatory Effects of Myeloid-Derived Suppressor Cell Exosomes in Mouse Model of Autoimmune Alopecia Areata - Zöller, Margot; Zhao, Kun; Kutlu, N. Natali; Bauer, Nathalie; Provaznik, Jan; Hackert, Thilo; Schnölzer, Martina (Frontiers in Immunology, 2018)
The treatment of autoimmune diseases still poses a major challenge, frequently relying on non-specific immunosuppressive drugs. Current efforts aim at reestablishing self tolerance using immune cells with suppressive activity like the regulatory T cells (Treg) or the myeloid-derived suppressor cells (MDSC). We have demonstrated therapeutic efficacy of MDSC in mouse Alopecia Areata (AA). In the same AA model, we now asked whether MDSC exosomes (MDSC-Exo) can replace MDSC. MDSC-Exo from bone marrow cells (BMC) cultures of healthy donors could substantially facilitate treatment. With knowledge on MDSC-Exo being lim¬ited, their suitability needs to be verified in advance. Protein marker profiles suggest comparability of BMC- to ex vivo collected inflam¬matory MDSC/MDSC-Exo in mice with a chronic contact dermatitis, which is a therapeutic option in AA. Proteome analyses substantiated a large overlap of function-relevant molecules in MDSC and MDSC-Exo. Furthermore, MDSC-Exo are taken up by T cells, macrophages, NK and most avidly by Treg and MDSC-Exo uptake exceeds binding of MDSC themselves. In AA mice, MDSC-Exo preferentially tar¬get skin-draining lymph nodes and cells in the vicinity of remnant hair follicles. MDSC-Exo uptake is accompanied by a strong increase in Treg, reduced T helper proliferation, mitigated cytotoxic activity and a slight increase in lymphocyte apoptosis. Repeated MDSC-Exo appli¬cation in florid AA prevented progression and sufficed for partial hair regrowth. Deep sequencing of lymphocyte mRNA from these mice revealed a significant increase in immu¬noregulatory mRNA, including FoxP3 and arginase 1. Downregulated mRNA was preferentially engaged in prohibiting T cell hyperreactivity. Taken together, proteome analysis provided important insights into potential MDSC-Exo activities, these exosomes preferentially homing into AA-affected organs. Most importantly, changes in leukocyte mRNA seen after treatment of AA mice with MDSC-Exo sustainably supports the strong impact on the adaptive and the non-adaptive immune system, with Treg expansion being a dominant feature. Thus, MDSC-Exo could potentially serve as therapeutic agents in treating AA and other autoim¬mune diseases.